A study of the relationship between cognitive diversity and dicision making outcomes and the role of task conflict as the moderator of the relationship [electronic resource] - Nur Azimah Mohd. Bakri, 1988-, author (2015)
Thesis (Sarjana Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2015